Impact of digital technology on herders’ grassland leasing-in decisions in Inner Mongolia, China - Chen Xue; Mei Yong; Fulin Du; Zhidong Feng; Jiali Han; Haihua Lin (PLoS ONE, 2025)
Against the backdrop of grassland ecological degradation, grassland transfer has become a crucial pathway for optimizing livestock resource allocation and promoting sustainable pastoral development. Based on survey data from 383 herder households in the farming–pastoral ecotone of Inner Mongolia, China, this study applies Heckman models, mediation models, and moderation models to examine the impact of digital technology on herders’ grassland leasing-in decisions and the underlying mechanisms. The results indicate that digital technology significantly increases both the probability and the scale of grassland leasing-in among herders. Moreover, digital technology indirectly promotes grassland leasing-in by enhancing scale efficiency. Notably, strong social networks weaken the facilitating role of digital technology in grassland transfer, whereas weak social networks strengthen it. The impact of digital technology on grassland leasing-in is especially pronounced under environmental regulations with weak incentives but strong constraints. Finally, compared with ordinary herders, digital technology has a significantly positive effect on grassland leasing-in only for new-type operators. In addition, the impact of digital technology is more pronounced among groups with higher levels of education.